2016
DOI: 10.1016/j.msea.2016.08.123
|View full text |Cite
|
Sign up to set email alerts
|

Stability of martensite with pulsed electric current in dual-phase steels

Abstract: Softening frequently occurs in dual-phase steels under isothermal tempering of martensite.Recently, non-isothermal tempering is implemented to decrease the softening process in dualphase steels. Here, we have discovered using high power electropulsing treatment can significantly enhance the strengthening effects via the formation of ultrafine-grained ferrite with nano-cementite particles in tempered martensitic-ferritic steels. To the best our knowledge, electropulsing treatment is a proper candidate to retard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 41 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Lu et al found that the mechanical properties of dual phase steel (DP600) were significantly improved by EPT-tempering [ 115 ]. The tensile strength increased by 38.98%, yield strength by 8.90% and hardness by 20.9%, presumably due to the formation of nano-cementite particles in the ultra-fine ferrite grains.…”
Section: Effects Of Ept On the Properties Of Materialsmentioning
confidence: 99%
“…Lu et al found that the mechanical properties of dual phase steel (DP600) were significantly improved by EPT-tempering [ 115 ]. The tensile strength increased by 38.98%, yield strength by 8.90% and hardness by 20.9%, presumably due to the formation of nano-cementite particles in the ultra-fine ferrite grains.…”
Section: Effects Of Ept On the Properties Of Materialsmentioning
confidence: 99%
“…The electrical resistance of the sample without inclusion is 2.5×10 −4 Ω. The average electric current density is 2.0×10 9 A·m −2 , which is in the same order as that used in many electropulsing processing experiments [12,13] but is at least 3 orders of magnitude smaller than the current-induced magnetization switching [14]. An electrically neutral inclusion with radius r i and electrical conductivity σ i = ησ m is embedded in the metal matrix with its centre in the distance from the centre of the matrix vertically (Fig.…”
Section: Numerical Calculation and Resultsmentioning
confidence: 72%
“…The influence of the electric current on the diffusivity and the free energy allows the electric current to accelerate the structural relaxation. Experiments have shown the electric effects on the hardness, tensile property, residual stresses, microstructures and dislocation density of quenched mediumcarbon steels [49] and the martensite phase in dual-phase steels [50]. The wear resistance and the corrosion behaviour in deep cryogenically treated steels have been modified due to the accelerated diffusivity of the carbon in the formation and the configuration of carbides [51].…”
Section: Electric Effect On Temperingmentioning
confidence: 99%